2022
DOI: 10.1007/s11739-021-02906-6
|View full text |Cite
|
Sign up to set email alerts
|

SIMEU position paper on non-invasive respiratory support in COVID-19 pneumonia

Abstract: The rapid worldwide spread of the Coronavirus disease (COVID-19) crisis has put health systems under pressure to a level never experienced before, putting intensive care units in a position to fail to meet an exponentially growing demand. The main clinical feature of the disease is a progressive arterial hypoxemia which rapidly leads to ARDS which makes the use of intensive care and mechanical ventilation almost inevitable. The difficulty of health systems to guarantee a corresponding supply of resources in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…This could prove to be challenging in some settings, particularly in low and middle income countries or settings that are acutely impacted by pandemic-related surges or supply shortages. Implementation of monitoring practices seen in the existing clinical trials may not be completely generalizable or feasible to clinical settings outside of the ICU where provider-patient ratios are higher 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This could prove to be challenging in some settings, particularly in low and middle income countries or settings that are acutely impacted by pandemic-related surges or supply shortages. Implementation of monitoring practices seen in the existing clinical trials may not be completely generalizable or feasible to clinical settings outside of the ICU where provider-patient ratios are higher 2 .…”
Section: Discussionmentioning
confidence: 99%
“…No studies specified patient outcomes or source of infection associated with any particular SARS-COV-2 variants of concern. It has been suggested that use of non-invasive ventilation strategies may increase transmission of SARS-COV-2 to healthcare workers, placing them at risk during care and adding strain to the healthcare system when isolation is required 2,26 . Although appropriate personal protective equipment may provide adequate protection for some healthcare workers when NIV strategies are used, existing studies are predominantly from early 2020 there is a lack of comparative studies available on this topic [67][68][69][70][71][72][73][74][75][76][77][78] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations